10 terms

y=-f(x)

reflecting the graph in the x axis

y=f(-x)

reflecting the graph in the y axis

y=f(3x)

stretching the graph by a factor of 1/3, parallel to the x axis

y=f(1/2x)

stretching the graph by a factor of 2, parallel to the x axis

y=3f(x)

stretching the graph by a factor of 3, parallel to the y axis

y=1/2f(x)

stretching the graph by a factor of 1/2, parallel to the y axis

y=f(x+1)

translating the graph by 1 unit left horizontally

y=f(x-1)

translating the graph by 1 unit right horizontally

y=f(x)+1

translating the graph by 1 unit up vertically

y=f(x)-1

translating the graph by 1 unit down vertically